Prosody in Elicitations: A Study of Intonation in BBC Talk Radio Shows - Herczeg-Deli Ágnes (Romanian Journal of English Studies, 2012)
The paper is concerned with the prosodic features of non-literal language use in indirect elicitations in radio talk. It will be demonstrated how intonation becomes mirror of some contextual factors, and how the prosodic features of elicitations can corroborate the speaker’s meaning manifested through certain lexico-grammatical elements in the discourse.